2014
DOI: 10.1089/aid.2014.0072
|View full text |Cite
|
Sign up to set email alerts
|

Albuminuria Is Associated with Elevated Acute Phase Reactants and Proinflammatory Markers in HIV-Infected Patients Receiving Suppressive Combination Antiretroviral Therapy

Abstract: Albuminuria among HIV-infected individuals has been found to be associated with cardiovascular disease (CVD) and mortality. Inflammation has been associated with albuminuria. The pathophysiology of albuminuria in HIV-infected individuals is poorly understood. We investigated the association of albuminuria with inflammatory biomarkers among HIV-infected individuals on combination antiretroviral therapy (cART). This is a cross-sectional analysis of participants enrolled in the Hawaii Aging with HIV-Cardiovascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Although there is overwhelming evidence of an association between UACR and endothelial dysfunction in different clinical settings 40 41 , this association was little explored in HIV positive patients 21 22 . O-Charoen et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although there is overwhelming evidence of an association between UACR and endothelial dysfunction in different clinical settings 40 41 , this association was little explored in HIV positive patients 21 22 . O-Charoen et al .…”
Section: Discussionmentioning
confidence: 99%
“…O-Charoen et al . 21 found that elevation of endothelial dysfunction markers, like soluble E-selectin and vascular cell adhesion protein-1, were significantly associated with albuminuria after adjustment for CV risk factors in HIV-infected patients receiving suppressive combination antiretroviral therapy 21 . However, Gupta et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 25 In 85% of HIV-infected adults taking TDF-based ART, the presence of albuminuria was associated with inflammatory biomarkers. 26 Nevertheless, the authors did not adjust for all baseline characteristics such as the use of angiotensin receptor blockers or angiotensin converting enzyme inhibitors, age and hypertension. Inflammatory biomarkers in another study 27 were higher in untreated HIV-infected participants compared to both HIV-infected participants (TDF-based ART and virally suppressed) and uninfected controls.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-infected individuals on stable ART show higher rates of albuminuria, as compared to the general population. Chronic low-grade inflammation may contribute to the development of albuminuria and renal dysfunction, which both pro-inflammatory and pro-fibrotic responses are important components [ 18 , 20 , 40 46 ]. However, mechanisms of albuminuria that occurs during ART-treated chronic HIV infection have been primarily focused on the pro-inflammatory arm.…”
Section: Discussionmentioning
confidence: 99%